RETRACTION NOTICE TO “Analysis of the Bachelor of Physical Education (BPEd) Program Prospectus through Course Content Assessment” - Lobo, Joseph; Bernardo, Bryan Dale (International Journal of Multidisciplinary: Applied Business and Education Research, 2022)
This article entitled “Analysis of the Bachelor of Physical Education (BPEd) Program Prospectus through Course Content Assessment” (2022), authored by Joseph Lobo and Bryan Dale Bernardo, published in Vol. 3, No. 11 of International Journal of Multidisciplinary: Applied Business and Education Research. 3(11), 2303 – 2315 has been retracted as requested by the authors.